2014
DOI: 10.1016/j.etp.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of connexin 32 in acetaminophen toxicity in a knockout mice model

Abstract: Gap junctional intercellular communication (GJIC), by which glutathione (GSH) and inorganic ions are transmitted to neighboring cells, is recognized as being largely involved in toxic processes of chemicals. We examined acetaminophen (APAP)-induced hepatotoxicity clinicopathologically using male wild-type mice and mice lacking the gene for connexin32, a major gap junction protein in the liver [knockout (Cx32KO) mice]. When APAP was intraperitoneally administered at doses of 100, 200, or 300mg/kg, hepatic centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…At 100 and 200 mg/kg APAP injected intraperitoneally, increased ALT quantities and more pronounced necrotic cell death were observed in Cx32 −/− animals. These effects were, however, not seen at 300 kg/mg APAP (Igarashi et al 2014), a commonly used dose for experimental testing purposes (Harril et al 2009; McGill et al 2012; Mossanen and Tacke 2015), which is in line with the findings of our study. With the exception of a lower hepatic amount of IL-1β after 0 and 6 hours and rather fortuitous variations in IL-10 and IFNγ amounts at a single time point, we also failed to detect modifications in serum and liver pro-inflammatory and anti-inflammatory cytokine levels in Cx32-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…At 100 and 200 mg/kg APAP injected intraperitoneally, increased ALT quantities and more pronounced necrotic cell death were observed in Cx32 −/− animals. These effects were, however, not seen at 300 kg/mg APAP (Igarashi et al 2014), a commonly used dose for experimental testing purposes (Harril et al 2009; McGill et al 2012; Mossanen and Tacke 2015), which is in line with the findings of our study. With the exception of a lower hepatic amount of IL-1β after 0 and 6 hours and rather fortuitous variations in IL-10 and IFNγ amounts at a single time point, we also failed to detect modifications in serum and liver pro-inflammatory and anti-inflammatory cytokine levels in Cx32-deficient mice.…”
Section: Discussionsupporting
confidence: 92%
“…Several signaling cascades are known to underlie APAP-induced liver toxicity, yet little is known about the involvement of GJIC. A limited number of reports have described a role for Cx32-based gap junctions in APAP-triggered hepatotoxicity using genetically modified animals, albeit with contradicting outcome (Igarashi et al 2014; Naiki-Ito et al 2010). In this respect, Naiki-Ito and colleagues administered up 1000 mg/kg APAP intragastrically to rats carrying a mutated Cx32 gene and noticed decreased ALT serum levels and lowered histopathological damage after 24 hours (Naiki-Ito et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, Mathieu et al previously investigated Cx32 hemichannels facilitate the apoptotic-to-necrotic transition, which typically occurs in the final stage of hepatocellular apoptosis [37]. On the other hand, Isao et al demonstrated that Cx32 protects against acetaminophen-induced hepatic centrilobular necrosis in mice [38]. Although seemingly paradoxical, these results may all be correct depending on the cells examined and the type of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although being critical mediators of liver homeostasis (Maes et al, 2015a), connexins and their channels are also frequently involved in liver toxicity (Maes et al, 2015b). A number of studies have shown a role for Cx32-based gap junctions in APAP-triggered hepatotoxicity using genetically modified animals, albeit with contradicting outcomes (Igarashi et al, 2014; Maes et al, 2016b; Naiki-Ito et al, 2010; Park et al, 2013). In a recent study, our group questioned the suitability of genetically deficient rodents for investigating the involvement of Cx32 in APAP-induced hepatotoxicity (Maes et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%